Relieving the Photosensitivity of Organic Field‐Effect Transistors. Issue 4 (29th November 2019) - Liu, Jie; Jiang, Longfeng; Shi, Jia; Li, Chunlei; Shi, Yanjun; Tan, Jiahui; Li, Haiyang; Jiang, Hui; Hu, Yuanyuan; Liu, Xinfeng; Yu, Junsheng; Wei, Zhongming; et al.
Abstract: It is generally believed that the photoresponse behavior of organic field‐effect transistors (OFETs) reflects the intrinsic property of organic semiconductors. However, this photoresponse hinders the application of OFETs in transparent displays as driven circuits due to the current instability resulting from the threshold voltage shift under light illumination. It is necessary to relieve the photosensitivity of OFETs to keep the devices stable. 2, 6‐diphenyl anthracene thin‐film and single‐crystal OFETs are fabricated on different substrates, and it is found that the degree of molecular order in the conducting channels and the defects at the dielectric/semiconductor interface play important roles in determining the phototransistor performance. When highly ordered single‐crystal OFETs are fabricated on polymeric substrates with low defects, the photosensitivity ( P ) decreases by more than 10 5 times and the threshold voltage shift (Δ V T ) is almost eliminated compared with the corresponding thin‐film OFETs. This phenomenon is further verified by using another three organic semiconductors for similar characterizations. The decreased P and Δ V T of OFETs ensure a good current stability for OFETs to drive organic light‐emitting diodes efficiently, which is essential to the application of OFETs in flexible and transparent displays. Abstract : The correlation of photosensitivity of organic field‐effect transistors (OFETs) to organic semiconductor bulk traps and semiconductor/dielectric interface traps is established and verified by systematical experimental studies. Highly ordered single crystals in combination with polymer dielectrics having low surface trap densities can ensure constant brightness output for series‐connected OFET‐driven organic light‐emitting diodes.